Effect of Continuous Renal Replacement Therapy on Multi-dimensional Serum Biomarkers (IL-4, Presepsin, NGAL, PD-L1, IL-10, Ang-2, sTM, histones, mtDNA, ADM, and suPAR levels ) and Clinical Symptoms in Patients with Sepsis: CRRT effects on multi-dimensional biomarkers in sepsis - Shen, Tao (Journal of Medical Biochemistry, 2026)
Objective: To investigate the effects of continuous renal replacement therapy (CRRT) on traditional and novel multi-dimensional serum biomarkers including inflammatory cytokines, immune regulation markers, endothelial injury markers, cellular damage indicators, and clinical symptoms in patients with sepsis. Method: A retrospective collection was conducted on 116 sepsis patients treated with CRRT in the hospital from March 2019 to June 2024 as the observation group; 219 sepsis patients who received conventional treatment during the same period were matched with propensity score in a 1:1 ratio, and 116 patients were selected as the control group. Two groups of patients were observed and compared for TNF-α, IL-4, CRP, Presepsin, IL-6, NGAL, PD-L1, IL-10, mHLA-DR, Ang-2, sTM, histones, mtDNA, ADM, suPAR, and clinical symptom related indicators after treatment. COX regression analysis was utilized to investigate the influencing factors of 28 d survival in sepsis patients after treatment. Results: After treatment, the TNF-α, IL-4, CRP, Presepsin, IL-6, NGAL, PD-L1, IL-10, Ang-2, sTM, histones, mtDNA, ADM, and suPAR levels in the observation group were significantly lower than those in the control (*p*<0.05), while mHLA-DR expression was higher (*p*<0.05). The acute physiology and chronic health (APACHE II) score, sequential organ failure score (SOFA), body temperature, heart rate, and respiratory rate (RR) levels in the observation were also lower than control, but the oxygenation index (PaO 2 /FiO 2 ) and urine output were higher (*p*<0.05). After 28d-treatment, the survival rates of patients in the control and observation were 65.52% and 81.90%. In COX analysis, septic shock, lactate, IL-4, CRP, Presepsin, IL-6, PD-L1, Ang-2, APACHE II score, RR, PaO 2 /FiO 2 , and CRRT were all factors affecting the 28 d survival of sepsis patients after treatment. Conclusion: During routine treatment of sepsis patients, CRRT can comprehensively alleviate inflammatory reactions, improve immune dysfunction, reduce endothelial and cellular damage, promote the elimination of sepsis related symptoms, and occupy a vital position in improving patient prognosis through multi-dimensional biomarker modulation.